Quality of child care using the environment rating scales: A meta-analysis of international studies - Vermeer, Harriet J.; van IJzendoorn, Marinus H.; Cárcamo, Rodrigo A.; Harrison, Linda J. (My University, 2016)
The current study provides a systematic examination of child care quality around the globe, using the Environment Rating Scales (ERS). Additional goals of this study are to examine associations between ERS process quality and structural features (group size, caregiver-child ratio) that underpin quality and between ERS and more proximal aspects of child care quality (caregiver sensitivity). Furthermore, we consider possible differences in ERS associations arising from scale characteristics (infant vs early childhood version, original version vs revised scale, full version vs shortened version). The reported meta-analysis combines results of ERS child care quality reported in 72 studies from 23 countries across five international geographic regions.Group center care appeared to be of average quality with higher quality levels in Australia/New Zealand and North America. Our results suggest that: (1) ERS characteristics are not associated with differences in ERS scores and (2) ERS scores are related to indicators of proximal quality of care (caregiver sensitivity) and, to a lesser degree, structural quality of care (caregiver-child ratio). The meta-analysis provided cross-cultural comparisons on child care quality on a common instrument as a means to advance discussion on child care quality internationally.
Keywords: center care; child care quality; environment rating scales; international